The physical quality test formulation of ethyl acetate extract of kawista fruit peel (Limonia Acidissima L.) Ointment as an antibacterial against propionibacterium acnes - Megawati Megawati; Yuniharce Kadang (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Using medicinal plants in Indonesia still needs to be optimized. Almost all parts of the Kawista plant have been traditionally used to treat various ailments such as antioxidants, antidiabetic, wound healing, and controlling uric acid levels. Existing research on Kawista fruit peel as an acne antibacterial includes studies on the ethyl acetate extract of Kawista fruit peel against Propionibacterium acnes, which falls into the moderate to strong category. In Indonesia, Kawista fruit is limited to the flesh and is used to make syrup and dodol (a traditional sweet). In contrast, the fruit's peel remains a waste product. Objective: This study aims to develop a formula for an ethyl acetate extract ointment of Kawista fruit peel (Limonia acidissima L.) as an antibacterial agent against Propionibacterium acnes with good physical quality. Methods: The fruit peel extract was obtained using the maceration method with 96% ethanol. The extract was then formulated into ointment preparations with concentration variations of 6.25% (F1), 12.50% (F2), and 25% (F3). The physical stability tests for the ointment included organoleptic parameters, homogeneity, spreadability, and pH value tests. The data were analyzed to determine the effect of the extract concentration and storage time on the ointment's physical stability. Result: The test results showed that the ointment formulation of Kawista fruit peel extract (Limonia acidissima L.) could be successfully formulated into an ointment form and met the required evaluation criteria, including organoleptic testing, homogeneity testing, pH testing, and spreadability testing. Conclusion: Based on the study, it can be concluded that the Kawista fruit peel extract ointment (Limonia acidissima L.) can be successfully formulated into an ointment and meets the required evaluation criteria, including organoleptic testing, homogeneity testing, pH testing, and spreadability testing. A skin irritation test is required to determine whether any irritation occurs after applying the ointment.